To find the distance between the points \((-16, 10)\) and \((-4, -6)\), we can use the distance formula, which is given by:
\[ d = \sqrt{(x_2 - x_1)^2 + (y_2 - y_1)^2} \]
Where \((x_1, y_1)\) and \((x_2, y_2)\) are the coordinates of the two points.
In this case:
- \((x_1, y_1) = (-16, 10)\)
- \((x_2, y_2) = (-4, -6)\)
Now, we can plug in the values:
-
Calculate \(x_2 - x_1\): \[ x_2 - x_1 = -4 - (-16) = -4 + 16 = 12 \]
-
Calculate \(y_2 - y_1\): \[ y_2 - y_1 = -6 - 10 = -16 \]
-
Now substitute these into the distance formula: \[ d = \sqrt{(12)^2 + (-16)^2} \]
-
Calculate \(12^2\) and \((-16)^2\): \[ 12^2 = 144 \] \[ (-16)^2 = 256 \]
-
Combine these results: \[ d = \sqrt{144 + 256} = \sqrt{400} \]
-
Finally, take the square root: \[ d = 20 \]
Therefore, the distance between the points \((-16, 10)\) and \((-4, -6)\) is \(\boxed{20}\).